â€œKERAJINAN LAMPU LOGAMâ€ (STUDI KASUS DI PERAJIN BAPAK UTUR SUDRAJAT DESA MAJENANG KECAMATAN SUKODONO KABUPATEN SRAGEN) - Kurniawan, Adi (ART EDUCARE Pendidikan Seni Rupa, 2013)
Abstract Abstract: Adi Kurniawan. ?METAL LAMP CRAFT? (A Case Study on Mr. Tutur Sudrajat Crafter in Majenang Village Sukodono Subdistrict Sragen Regency), Thesis. Surakarta: Teacher Training and Education of Surakarta Sebelas Maret University, January, 2013. The objective of research is to find out: 1) background of Mr. Tutur Sudrajat?s metal lamp craft establishment, (2) material and tools as well as process used, (3) design motive applied to metal lamp craft, and (4) finishing technique used. The strategy used was a single embedded case study. The data sources used were informant, place and event, document and literature. Techniques of collecting data used were interview, observation, and documentation. The sampling technique used was purposive sampling. Data validation was done using data triangulation and review informant. Techniques of analyzing data used were interactife: data reduction, data display, and conclusion drawing or verification. Considering the result of research, the following conclusion could be drawn. (1) The background of metal lamp craft establishment departed from Mr. Tutur hobby who loved art since he was very young. For that reason, he wanted to create the ornamental lamp with his own creation and attempted to make ornamental lamp with unique and different design motive, and finally, it is known as Metal Lamp Craft Ethnic. (2) The material and tools as well as process used in producing included: 2.1) Materials. a) main material: plate, carbon paper, treatment liquid, mica, lamp, cable, electrical plug, fitting, screw and bolt. b) supporting material: oil, glue. c) finishing material: putty, paint, thinner, stretch-resistant plastic, packing cardboard. 2.2) The tools used were: pencil, ballpoint, ruler, meter tape, U saw, jig saw, and mini drill, hand drill, stand drill, electric weld, cutter grinder, grinder, rived pincer, file, pincer, metal cutter, acrylic cutter, hammer, metal scissor, compass, sandpaper, screwdriver, brush, kanebo, compressor, spray gun, hair dryer. 2.3) The production process: preparing tool and material, preparing design mall, cutting the plate, moving the mall design into plate, cutting, sandpapering, making the hole for screw and bolt, metal folding, plat washing using treatment liquid, drying, drying heating, brushing, putty, priming up to finishing painting, paint drying, the installation of lamp fitting, cable, electric plug, mica, anterior, lamp covers installation, and packing, (3) the design motive applied to metal lamp craft included: a) pakem batik motif, b) contemporary batik motif, c) puppet motif, d) modern motif, e) ball logo motif, f) calligraphy motif, g) cartoon, (4) finishing technique used in producing metal lamp craft included: putty, sandpapering, painting, drying, and packaging. Keywords: craft, work, metal, batik, motif, design